Completing the Legislation of Crime in Vietnam's Current Criminal Law - Cam, Le (VNU Journal of Science: Legal Studies; Vol 34 No 1DO - 10.25073/2588-1167/vnuls.4136, 2018)
The article analyzes the situation and points out some shortcomings of the legislation of crime in the current Criminal Code (the Penal Code 2015) (12 articles from Article 8 to Article 19) as well as proposes a solution to continue improving Vietnam Criminal Law in the future with a  legislative model including: 1) Keep stable 03 articles (13, 18-19); 2) Transfer 01 article (Article 13 Penal Code 2015) to the new Independent Chapter on Criminal Responsibility (needs to be added to the Penal Code in the future) accordingly; 3) Add 11 more new articles to complete the legislation of crime. Keywords Legislation, crime, Penal Code 2015, Criminal Law in the future, Legislative Model References [1] Lê Văn Cảm, Nguyễn Thị Lan. Nghiên cứu các luận điểm từ lý luận về lập pháp hình sự trong Nhà nước pháp quyền. Tạp chí Khoa học - Chuyên san Luật học, số 3/2017. [2] Hiến pháp Việt Nam năm 2013. [3] Bộ luật hình sự Việt Nam năm 2015 (sửa đổi, bổ sung năm 2017). [4] Lê Văn Cảm, Luật hình sự Việt Nam và sự nghiệp xây dựng Nhà nước pháp quyền: Một số vấn đề hoàn thiện các quy phạm của Phần chung. Tạp chí Toà án nhân dân, số 9/1997.